2000
DOI: 10.1002/pri.196
|View full text |Cite
|
Sign up to set email alerts
|

Manual hyperinflation — Effects on respiratory parameters

Abstract: MH performed in the stable ventilated patient significantly increased CL and PaO2:FIO2 and decreased (A-a)PO2, but the clinical significance of this improvement is unclear. Further investigations are required to validate the findings of this study as well as to determine the therapeutic value of MH on patient outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 19 publications
(24 reference statements)
1
46
1
2
Order By: Relevance
“…They used a self-inflating Laerdal (Laerdal Medical, Norway) resuscitation bag and found no significant improvements in oxygenation. The studies 3,4 in which oxygenation showed improvement used a Mapleson circuit (Mapleson "C" circuit and a 2 L reservoir bag [BS 3352, Warne Surgical Products Ltd, Lurgan, Ireland]. In the present study, although a self-inflating Intersurgical resuscitation bag (Intersurgical Ltd, Berkshire, UK) was used, significant improvements in oxygenation were found after MHI, which persisted significantly above baseline at 20 minutes after hyperinflation.…”
Section: Discussionmentioning
confidence: 35%
See 1 more Smart Citation
“…They used a self-inflating Laerdal (Laerdal Medical, Norway) resuscitation bag and found no significant improvements in oxygenation. The studies 3,4 in which oxygenation showed improvement used a Mapleson circuit (Mapleson "C" circuit and a 2 L reservoir bag [BS 3352, Warne Surgical Products Ltd, Lurgan, Ireland]. In the present study, although a self-inflating Intersurgical resuscitation bag (Intersurgical Ltd, Berkshire, UK) was used, significant improvements in oxygenation were found after MHI, which persisted significantly above baseline at 20 minutes after hyperinflation.…”
Section: Discussionmentioning
confidence: 35%
“…2 Manual hyperinflation (MHI) is known to improve pulmonary compliance and oxygenation (PaO 2 : FIO 2 ). 3,4 Ventilator hyperinflation (VHI), on the other hand, is a newer technique and comparatively less popular than MHI. Yet, few studies comparing MHI and VHI have found VHI to be an equally beneficial 5 alternative of MHI or even a better alternative than MHI.…”
mentioning
confidence: 99%
“…It has been shown that the use of respiratory physiotherapy techniques can reduce pulmonary secretion retention, (1,3) as well as improving dynamic compliance (4) and static compliance. (5,6) One of a number of respiratory physiotherapy techniques, MH is commonly used by physiotherapists in patients receiving MV. (5) Originally called "bag squeezing", MH consists of a series of deep breaths with a three-second inspiratory pause combined with expiratory rib cage compression (ERCC) and suctioning.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is commonly used to prevent and reverse atelectasis, 3 increase alveolar ventilation, 4 and mobilize secretions so they may be suctioned. 5,6 MHI has been shown to result in improvements in static and dynamic lung compliance, an increased yield of secretions, 2,4,5,7,8 and a trend in reducing ventilator-associated pneumonia. 9 Movement of secretions in intubated patients occurs by the process of annular 2-phase gas-liquid flow.…”
mentioning
confidence: 99%